2010
DOI: 10.1002/iroh.200911174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eutrophication on Flagellates Associated with Eichhornia crassipes: An Experimental Approach

Abstract: The effects of nutrient enrichment on density, biomass and on the relative contribution of pigmented and heterotrophic flagellates to the total abundance of all flagellates associated with Eichhornia crassipes were evaluated through mesocosm experiments over 33 days. Two triplicate treatments (nitrogen and phosphorus addition and a control treatment) were colonized, producing six mesocosm systems. The only variable that showed significance was flagellate density. Density increased significantly with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the B− habitat, as the content of biogenic substances decreased, so did the abundance of ciliates. Bauer et al, Pereira et al and Buosi et al also showed a strong relationship between abundance and the availability of nutrients [43,51,52]. Such correlations were also observed by Mieczan and Tarkowska-Kukuryk and by Mieczan et al [26,50].…”
Section: Effect Of Restoration On the Composition And Abundance Of Ci...mentioning
confidence: 63%
“…In the B− habitat, as the content of biogenic substances decreased, so did the abundance of ciliates. Bauer et al, Pereira et al and Buosi et al also showed a strong relationship between abundance and the availability of nutrients [43,51,52]. Such correlations were also observed by Mieczan and Tarkowska-Kukuryk and by Mieczan et al [26,50].…”
Section: Effect Of Restoration On the Composition And Abundance Of Ci...mentioning
confidence: 63%